2012
DOI: 10.1128/jvi.00073-12
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for RNA Binding and Homo-Oligomer Formation by Influenza B Virus Nucleoprotein

Abstract: Influenza virus nucleoprotein (NP) is the major component of the viral ribonucleoprotein complex, which is crucial for the transcription and replication of the viral genome. We have determined the crystal structure of influenza B virus NP to a resolution of 3.2 Å. Influenza B NP contains a head, a body domain, and a tail loop. The electropositive groove between the head and body domains of influenza B NP is crucial for RNA binding. This groove also contains an extended flexible charged loop (amino acids [aa] 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
60
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 32 publications
1
60
0
3
Order By: Relevance
“…It is possible that the mutations investigated in this study affected the structure of the protein such that multiple functions of this region of BNP were affected. Unfortunately it is not possible to relate these functions to the structure of the protein, as this region of BNP is highly flexible and does not allow for X-ray crystallographic studies (23). The fact that the N-terminal extension of BNP is completely absent from the NP of influenza A viruses suggests that influenza A and B viruses have evolved different strategies for regulating transcription and replication of their genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the mutations investigated in this study affected the structure of the protein such that multiple functions of this region of BNP were affected. Unfortunately it is not possible to relate these functions to the structure of the protein, as this region of BNP is highly flexible and does not allow for X-ray crystallographic studies (23). The fact that the N-terminal extension of BNP is completely absent from the NP of influenza A viruses suggests that influenza A and B viruses have evolved different strategies for regulating transcription and replication of their genome.…”
Section: Discussionmentioning
confidence: 99%
“…One of the striking differences between the NP of these viruses is that the first 69 residues of BNP show no homology to those of ANP, and there is an evolutionarily conserved 50-amino-acid extension on the N terminus of BNP that is absent from ANP (14). The molecular structure of BNP recently has been solved, and interestingly, the entire N-terminal extension is missing from this structure due to the lack of electron density, suggesting that this region of BNP is highly flexible (23). Previous work reported that this N-terminal extension is not essential for nuclear accumulation of BNP or for the protein to function in an in vitro transcription/replication assay (14).…”
mentioning
confidence: 99%
“…For several negative-strand RNA viruses, assembly of the RNP has been shown to involve nucleocapsid protein polymerization to enwrap the entire viral RNA genome (43)(44)(45)(46)(47). Arenavirus nucleoprotein homo-oligomerization, which has been documented for members of both the Old World (LASV and LCMV) and New World (TCRV) groups, has been proposed to be an essential element for arenavirus RNP assembly (11,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…LASV NP is associated with multiple activities, including RNA binding, cap snatching, and an exonuclease activity related to immunosuppression (17)(18)(19). Lastly, the structure of the influenza virus NP is different from any of these NPs described above but is conserved within the Orthomyxoviridae family (1,(20)(21)(22). By comparison, NPs from −ssRNA viruses with nonsegmented genomes are usually related in both structure and function (1).…”
mentioning
confidence: 99%